1980
DOI: 10.1038/clpt.1980.136
|View full text |Cite
|
Sign up to set email alerts
|

Disposition of synthetic glucocorticoids: II. Dexamethasone in parturient women

Abstract: The plasma level: time profile for dexamethasone after dexamethasone phosphate 8 mg by intravenous bolus (n = 6) or intramuscular injection (n = 6) to pregnant women near term who were to undergo cesarean section was determined by high-performance liquid chromatography. Although pregnancy did not affect the terminal half-life (mean, 142 min; n = 10), the estimate of total plasma clearance was greater in pregnant (559 ml/min) than in nonpregnant women (243 ml/min). The umbilical/maternal venous plasma level rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
29
2

Year Published

1984
1984
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 0 publications
1
29
2
Order By: Relevance
“…Minor differences in the maternal and fetal plasma protein binding of these steroids in human (16,20,21), sheep (22) and rat (19) plasma do not explain the maternal/ fetal concentration gradient. This indicates that some disposition process restricts the fetal access of exogenous corticosteroids in these species.…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…Minor differences in the maternal and fetal plasma protein binding of these steroids in human (16,20,21), sheep (22) and rat (19) plasma do not explain the maternal/ fetal concentration gradient. This indicates that some disposition process restricts the fetal access of exogenous corticosteroids in these species.…”
Section: Introductionmentioning
confidence: 87%
“…Corticosteroid pharmacokinetic profiles after maternal drug administration in humans (16,17), sheep (5,18), and rats (19) show total fetal to maternal concentration ratios of less than 1 (Յ0.45). Minor differences in the maternal and fetal plasma protein binding of these steroids in human (16,20,21), sheep (22) and rat (19) plasma do not explain the maternal/ fetal concentration gradient.…”
Section: Introductionmentioning
confidence: 98%
“…Studies have demonstrated that synthetic glucocorticoids suppress plasma cortisol [1, 3, 4, 5]and ACTH [5]less efficaciously during pregnancy in humans. Although this suggests that increases in resting plasma cortisol concentration are caused by a reduced feedback suppression of ACTH [1], increases in adrenal responsiveness to ACTH [1]and/or increase in clearance of synthetic glucocorticoids [6]could also account for the apparent decrease in feedback sensitivity in humans.…”
Section: Introductionmentioning
confidence: 99%
“…The use of antenatal corticosteroids (ANS) in mothers of preterm infants delivered before 34 weeks of gestation is standard practice in perinatal medicine [6]. Significant immune attenuation can also be observed in mononuclear cells exposed in vitro to corticosteroid equivalents comparable to levels measured in serum of pregnant women after a standard ANS treatment [7,8,9,10]. However, when examining infants exposed to ANS, no effects were detected on cord blood IL-6 responses [9].…”
Section: Introductionmentioning
confidence: 99%